Pyrolysis of oil palm solid wastes - Farid Nasir Ani, 1957-; Wong, Chuan Chin; Regional Conference on Energy Technology Towards a Clean Environment (2nd : 2003 : Phuket, Thailand) (Skudai : Universiti Teknologi Malaysia, 2003)
50